Kalahari living on the edge ([Pretoria, R.S.A.] : Provision [production company] ; Johor Bharu : Oscar Triumph Sdn. Bhd. [distributor], 1998)
Explores the drama and fascinating variety of desert life and was filmed in the Kalahari Gemsbok National Park, where each animal and plant has adapted to survive the harsh climatic conditions
Executive producer, Fanie Van Der Merwe ; writer, Nicole Duplaix
Narrator: Pete Terry
VCD format
Keywords: Animals in motion pictures; Documentary films